TROP2-targeted NIR-II fluorescence imaging for visualizing surgical margins and metastatic sentinel lymph nodes in breast cancers - Kang-Liang Lou; Jing-Wen Bai; Hong-Tan Liu; Lin-Ling Lin; Cheng-Xi Li; Yi-Yang Gao; Sheng-Jie Lin; Yi-Fei Pei; Xiao-Long Wei; Yi-Xin Chen; Yi-Yin Tang; Hong-Yu Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
In early breast cancer surgery (EBC), free margins significantly decrease local recurrence in breast-conserving surgery (BCS), while metastatic status of sentinel lymph node (SLN) impacts axillary management. However, intraoperative visualization of margins and metastatic SLNs (mSLNs) remains challenging. Here, we report a second-window near-infrared (NIR-II) fluorescence probe by conjugating ICG to TROP2-targeting cyclic peptide (TTP-ICG). Our results showed that TTP-ICG specifically binds to TROP2-expressing cells in vitro and identifies TROP2-positive tumors in vivo. In addition, TTP-ICG enabled efficient intraoperative evaluation of surgical margins and visualization of mSLNs at a submillimeter level in preclinical models. Additionally, we optimized the rapid incubation imaging method (RIIM) by shortening the procedure to less than 8 min, illustrating TTP-ICG’s high performance in distinguishing malignant from normal tissues/fibroadenoma lesions as well as detecting metastatic lymph nodes in a cohort of 59 patients. Thus, this TROP2-targeting probe demonstrates its significance for fluorescence imaging-guided surgery with dual applicability in EBC, providing translational potential for further clinical decision-making.